Valoración de las actuaciones de atención educativa al alumnado inmigrante en Castilla y León - Rufino Cano González (Universidad de La Rioja, 2013)
The social communities surrounding us are characterized by a progressive growth of diverse cultures and values living together at their centre. In this aspect, our own community is no exception. The phenomenon of immigration is not something which exists only outside our borders. The social integration and education of immigrants has become a question of social interest which demands preferential attention from all administrative areas of the Government of Castilla y León. School, as one of the most responsible instances of society, is directly influenced by social and cultural factors and is also sensitive to the phenomenon of a multicultural society. We have devoted this article to analyzing and evaluating experiences and practices of intercultural education in schools.